Representation of masculinity on the main character in the novel "Selamat Tinggal" by tere liye - Fitri Anggun Lestari; Sugiarti Sugiarti (Kajian Linguistik dan Sastra, 2022)
Gender cannot be separated from masculinity and femininity. Masculinity which is a symbol ofmasculinity and leads to men is certainly interesting to study because the masculinity thatexists in each individual is certainly different. Masculinity can also occur in literary works asdocuments containing experiences, stories, and life, which are described by fiction charactersas plays in the storyline. This study aims to (1) describe the forms of masculinity and (2)explain the factors that cause masculinity in the main character in Tere Liye's SelamatDatang novel. Assessed by using a qualitative descriptive method. Data source of this researchis the novel and the research data is in the form of story units, sentences or paragraphsrelated to masculinity. Data collection was carried out by reading the novel and referencesobtained through relevant journals and books. Analysis of research data was carried out byclassifying the data, categorizing the data and finding important issues related to therepresentation of masculinity. The results of this study are the discovery of forms ofrepresentation of masculinity in the characters, namely (1) competitive, (2) independent, (3)easy to make decisions, (4) believe in their own abilities, (5) able to take risks. While thefactors causing Sintong's masculinity are (1) cultural factors, (2) social factors, and (3)personal factors. With that, this novel can be a source of reading to find out therepresentation of masculinity that occurs in the novel.Keywords: masculinity, main character, novel “Selamat Tinggal” by Tere Liye